Tectonic, geochronology, and volcanism in the Souther Rocky Mountains and Rio Grande rift. - 20160731 frey50; New Mexico Institute of Mining and Technology (Socorro, N.M. State of New Mexico, 2004)
Detailed gologic mapping, geophysics and expanded geochronology datasets provide important new insights into the volcanic and tectonic history of New Mexico and document a complex hisotry of Laramide-age faulting.
The fifteen papers included in this volume represent decades of research on the tectonic and volcanic history of the Shouther Rocky Mountains and the Rio Grande rift of New Mexico and Colorado.
Keywords: Geology - New Mexico and Colorado